PENGARUH STRUKTUR KEPEMILIKAN, STRATEGI DIVERSIFIKASI, LEVERAGE, FAKTOR INTERN DAN FAKTOR EKSTERN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIK PADA PERUSAHAAN MANUFAKTUR DAN NON MANUFAKTUR DI BURSA EFEK JAKARTA) - Sujoko Sujoko (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The main objective of the study is to examine the impact of ownership structure, diversification strategy, leverage, external factor, internal factor on the value of the firms in Jakarta Stock Exchange. It is argued that unlike the agency problem of advanced stock market, the agency problem in the Jakarta Stock Exchange is the divergence of interest between the minority holders and majority holders. This is because the Jakarta Stock Exchange is characterized, among other things, by the domination of large shareholders. The hypotheses are: (1) there are the impact of ownership structure, external factor, and internal factor on diversification strategy, (2) there are the impact of ownership structure, external factor, internal factor, and diversification strategy on leverage, (3) there are the impact of ownership structur, external factor, internal factor, leverage ,diversification strategy on value of the firm. This study is to examine Agency Theory, Jensen and Meckling (1976), Pecking Order Theory, Myers (1984), Trade Off Model and Signaling Theory (1979). Population in this study are public company listed in Jakarta Stock Exchange  during 2000 – 2004. As many as 134  firms listed in Jakarta Stock Exchange were taken as a sample using a purposive sampling method.The data were then analyzed by the structural equation modeling ( SEM) analysis, using the AMOS Program version 4.01.The results of this study show that (1) there are the impact of ownership structure, external factor, internal factor on diversification strategy, (2) there are the impact of ownership structure, diversification, external factor, internal factor on leverage,(3)there are the impact of ownership structure, external factor, internal factor, leverage, diversification on value  of the  firm. The result of the study does not support the Agency Theory, from Jensen and Meckling (1976), but the result of the study  supports  Pecking Order Theory from  Myers (1984),  Trade off model and Signaling Theory from Battacharya (1979). The result of the study is hoped to contribute theoretically and practically.Theoritical contribution is bounded to examine the Agency Theory from Jensen and Meckling (1976), Pecking Order Theory from Myers (1984), Trade off model and Signaling Theory from Battacharya (1979). The result of the study to indicate that  practice public company in Indonesia is not concern with Agency Theory from Jensen and Meckling (1976). The result of the study indicates that Pecking Order Theory from Myers (1984). Trade Off Model and Signaling Theory from Battacharya,(1979) are concerned with the practice public company in Indonesia.